Financing micro-entrepreneurs for poverty alleviation: A performance analysis of microfinance services offered by BRAC, ASA, and Proshika from Bangladesh - Dilruba Khanam; Muhammad Mohiuddin; Asadul Hoque; Olaf Weber (Journal of Global Entrepreneurship Research, 2018)
Microfinance services have emerged as an effective tool for financing micro-entrepreneurs to alleviate poverty. Since the 1970s, development theorists have considered non-governmental microfinance institutions (MFIs) as the leading practitioners of sustainable development through financing micro-entrepreneurial activities. This study evaluates the impact of micro-finance services provided by MFIs on poverty alleviation. In this vein, we examine whether microfinance services contribute to poverty alleviation, and also identify bottlenecks in micro-finance programs and operations. The results indicate that the micro-loans have a statistically significant positive impact on the poverty alleviation index and consequently improve the living standard of borrowers by increasing their level of income.
Keywords: C13; 650; Poverty alleviation; Microcredit; NGOs; Sustainable rural development; Developing country; Bangladesh